Design and evaluation of a pulsatile flow rotary vane blood pump. (June 2023) - Li, Mengtang
Artificial cardiovascular organs, termed as mechanical circulatory support (MCS) devices, provide patients with hemodynamics circulatory restoration effectively and vitally but yet are hampered by device-induced adverse events such as thrombotic, embolic and bleeding, which are consequences of blood being chronically exposed to non-pulsatile flow motion and high shear stress. A step forward to better assist heart failure patients, a novel MCS device was proposed aiming at generating a pulsatile blood flow under different systemic vascular resistance and imposing low shear stress on blood elements. Detailed design methods and geometry governing equations were derived first. For this human heart blood circulation application with a flowrate of0 − 6 LPM and pressure range around0 − 160 mmHg, a first-generation prototype with a positive displacement of21 . 7 mL / rev directly driven by a70 W brushless direct current (DC) motor was designed, manufactured and assembled. Computational fluid dynamics (CFD) simulations and bench top experiments were conducted next to characterize the MCS pump and to verify with mathematical models. Finally, the proposed MCS device-mediated hemolysis index was evaluated via CFD simulations and compared with an FDA-benchmark centrifugal MCS pump. This demonstrates potentially higher device hemocompatibility and paves the way for in vitro test in the future.